Cert Prep: Unity Certified Associate Game Developer Fundamentals. - Thorn, Alan (linkedin.com, 2021)
Become a Unity Certified Associate and show employers you have the Unity skills they're looking for. Study for the Fundamentals portion of the Unity certification exam.